2008
DOI: 10.1016/j.cell.2007.11.041
|View full text |Cite
|
Sign up to set email alerts
|

A β-arrestin 2 Signaling Complex Mediates Lithium Action on Behavior

Abstract: Besides their role in desensitization, beta-arrestin 1 and 2 promote the formation of signaling complexes allowing G protein-coupled receptors (GPCR) to signal independently from G proteins. Here we show that lithium, a pharmacological agent used for the management of psychiatric disorders such as bipolar disorder, schizophrenia, and depression, regulates Akt/glycogen synthase kinase 3 (GSK3) signaling and related behaviors in mice by disrupting a signaling complex composed of Akt, beta-arrestin 2, and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
367
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(386 citation statements)
references
References 52 publications
10
367
3
6
Order By: Relevance
“…The first option is unlikely as DA SNpc loss is estimated to be 60%–70% at the onset of symptoms (Fearnley & Lees, 1991; Lang & Lozano, 1998). Favoring the second option is the report that, after binding to D 2 receptors, dopamine can be internalized to form a signaling complex (including ß‐arrestin and protein phosphatase 2) that regulates the Akt pathway (Beaulieu et al, 2008), a cascade involved in neuroprotection (Dudek et al, 1997; Soler et al, 1999). Dopamine inhibits GABA A ‐mediated synaptic inputs to intrinsic striatal neurons (Bracci, Centonze, Bernardi, & Calabresi, 2002; Momiyama & Koga, 2001; Pisani, Bonsi, Centonze, Calabresi, & Bernardi, 2000) through presynaptic D 2 receptors (Centonze et al, 2003; for a review, see Berke, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The first option is unlikely as DA SNpc loss is estimated to be 60%–70% at the onset of symptoms (Fearnley & Lees, 1991; Lang & Lozano, 1998). Favoring the second option is the report that, after binding to D 2 receptors, dopamine can be internalized to form a signaling complex (including ß‐arrestin and protein phosphatase 2) that regulates the Akt pathway (Beaulieu et al, 2008), a cascade involved in neuroprotection (Dudek et al, 1997; Soler et al, 1999). Dopamine inhibits GABA A ‐mediated synaptic inputs to intrinsic striatal neurons (Bracci, Centonze, Bernardi, & Calabresi, 2002; Momiyama & Koga, 2001; Pisani, Bonsi, Centonze, Calabresi, & Bernardi, 2000) through presynaptic D 2 receptors (Centonze et al, 2003; for a review, see Berke, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While this has not yet been specifically assessed, it has been shown that these agents influence core members of the CME interactome 109 . Further, lithium and PUFAs also influence CME 115,118 . In terms of heritability, many genes have roles either directly or indirectly in CME or trafficking, including stonin2, epsin4, DTNBP1, muted, neuregulin, ERBB4, PP2B, calcineurin, KCNH2, DLG1 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…For other classes of antipsychotics, effects on receptor endocytosis are less clear 112 . The mood stabilizer lithium, which influences many signalling pathways [113][114] , has similar effects on -arrestin and the Akt/GSK-3 pathway 115 . Interestingly, clomipramine, and its active metabolite desmethylclomipramine have recently been shown to potently inhibit autophagic flux (PMID 19706685).…”
Section: First-and Second Generation Antipsychotics and Lithium Direcmentioning
confidence: 99%
“…As shown in Figure 1b and Supplementary Table 2, clozapine and olanzapine differed from haloperidol by virtue of their high-affinity interactions with most of the 14 human serotonin GPCRs and relatively lower affinity interactions with D2, D3, and D4 dopamine receptors. Furthermore, Figure 2a shows the lack of activity of clozapine at various protein kinases implicated in psychotherapeutic drug actions (eg, GSK3b, Erk1, Erk2, and Akt1) (Beaulieu et al, 2009;Beaulieu et al, 2008;Beaulieu et al, 2005). In passing, we note that clozapine was a moderately potent inhibitor of CHK2 (Figure 2b)Fa kinase involved in cell cycle regulation (Matsuoka et al, 1998).…”
Section: Clozapine Interacts With a Defined Subset Of Molecular Targetsmentioning
confidence: 99%